DINAMIKA POLA PENGUASAAN LAHAN SAWAH DI WILAYAH PEDESAAN DI INDONESIA - Winarso, Bambang (Politeknik Negeri Lampung., 2012)
Land ownership is an important factor for the Indonesian population who lives still depend on agriculture. Ownership of land is not only important for agriculture but also to assess the needs of others in their social life. So, land not only serves as an asset but can also function as a commodity that can be traded, it also serves as a social status for their owners. Land transactions, especially in rural areas, expansive effect on tenure and rural incomes, which may have implications for the emergence of a variety of land tenure in the countryside. The results PATANAS (Panel Petani Nasional) 2010 conducted by the Center for Social and Enonomi of Agriculture, over the period 2007 to 2010 shows that the country has decreased, especially in Java land, while the villages outside Java are experiencing the opposite of a sharp increase in ownership. This indicates that the Panel Petani Nasional for 3 (three) years, indicating that that in that period there has been a fluctuation in land ownership. Whilst the change is not so prominent, but the tunakisma (lendless) in rural areas are likely to continue to grow. This certainly has implications to changing socio-economic conditions for rural communities concerned, same with the changing status of tenure communities. This paper is part of research that focuses on PATANAS 2010 villages based producer of rice paddy fields as national Keywords: Pattern Dynamics Control, Wetland, Rural Areas